Accuracy of Conventional Digital Palpation and Ultrasound of the Cricothyroid Membrane in Obese Women in Labour. Issue 3 (September 2016) - You-Ten, K.E.; Desai, D.; Postonogova, T.; Siddiqui, N.
Abstract : ( Anaesthesia. 2015;70(11):1230–1234) The primary aim of this study was to determine the accuracy of identifying the cricothyroid membrane in women in labor using conventional digital palpation and ultrasonography. The study was undertaken at a teaching hospital in Canada and included "patient" and "participant" groups. The patient group included women between 37 and 40 weeks' gestation who were in labor. Twenty-eight obese (body mass index >30 kg/m 2 ) and 28 nonobese women were enrolled in the study. Demographic data including age, weight, and height along with morphometric measurements (neck circumference, thyromental distance and sternomental distance) were obtained. The participant group (n=10) included anesthesia staff, fellows, and residents working in the labor and delivery unit of the hospital. They were randomized to palpate the cricothyroid membrane of an obese or nonobese parturient. The study design allowed a participant to participate more than once. These participants were randomized each time they participated. Among these ten, three participants palpated the cricothyroid membrane of nonobese patients only and 7 palpated the cricothyroid membrane of both obese and nonobese patients. Years of training and experience in performing cricothyroidotomy were recorded for each participant. No one had performed a cricothyroidotomy within the previous 12 months before the study.